Hubungan Keberadaan Ruang Terbuka Hijau dengan Kualitas Udara di Kota Semarang - Galih Maulidia Nawangsari; Mussadun Mussadun (Ruang, 2018)
The biggest problem in Semarang City these days is the increase of population. This happenes because of the increase the birth rate and urbanization. The impact from this phenomenon is the need of spaces that encorage people to convert the land use of their area, mostly green space. In addition, an increasing number of the population is also increasing the number of motor vehicle which may cause air pollution. This condition imply that there is a relation between the avaibility of open green space with air quality in Semarang City. In this study, three sub-districts being choosen, which is Banyumanik sub-district, Pedurungan sub-district and Tugu subdistrict. These sub-districts, was choosen because they can represent every sector of their land use. Banyumanik sub-district represent central bussiness distirct, Pedurungan sub-distict represent settlement area and Tugu sub-district represent industrial area. Methods of analysis that used in this study is quantitative method, which is regretion analysis and descriptive quantitative analysis. The results of this study, it is known that there is a corelation between the open green space and air quality in Semarang city with every differences from each sub-district. The most influential parameter in Banyumanik sub-distric is CO, in Pedurungan sub-distric is O3 and in Tugu sub-district is dust. The expansion of open green space and the selection of appropiate vegetation for every sub-district are the right solution to make a better air quality in Semarang City.